Chitosan zinc oxide composite nanofiber humidity sensor and preparation method
Patent Information
- Application Number
- CN202611315472.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-27
- Publication Date
- 2026-10-23
AI Technical Summary
[0006]本发明的目的在于提供一种壳聚糖氧化锌复合纳米纤维湿度传感器及其制备方法,以解决现有湿度传感器灵敏度性能不佳的问题
1.本发明通过氨基硅烷偶联剂改性、磷酸改性和戊二醛交联的协同作用,实现了纳米氧化锌在壳聚糖中的均匀分散和牢固界面结合。通过氨基硅烷偶联剂和磷酸化改性对纳米氧化锌进行表面修饰,有效解决了纳米粒子在壳聚糖基体中的团聚问题;磷酸化改性纳米氧化锌与壳聚糖形成氢键,戊二醛分子上的醛基与壳聚糖分子链上的氨基发生氨醛缩合反应,形成亚胺键,界面结合强度远优于物理混合。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention belongs to the field of humidity sensor technology, specifically relating to a chitosan-zinc oxide composite nanofiber humidity sensor and its preparation method. Background Technology
[0002] Humidity sensors are widely used in automotive electronics, industrial control, healthcare, and environmental monitoring. In recent years, with the large-scale application of humidity sensors, some shortcomings of existing sensors have become apparent. Current humidity sensors are mainly classified into metal oxide type, polymer type, and composite material type.
[0003] Metal oxide humidity sensors mainly include aluminum oxide, titanium oxide, and zinc oxide. Among them, zinc oxide stands out due to its high sensitivity, good high temperature resistance, and mature process, but it has problems such as high energy consumption and poor long-term stability.
[0004] Polymer humidity sensors mainly include natural polymers such as chitosan and synthetic polymers such as polyimide. Among them, chitosan has attracted widespread attention due to its advantages such as strong hydrophilicity, rich hydroxyl and amino groups in its molecular chain, good biocompatibility, and low cost. However, chitosan alone has defects such as poor long-term stability, severe swelling under high humidity, and slow response speed, which seriously restricts the application of chitosan.
[0005] Composite material humidity sensors primarily combine two or more materials to compensate for the deficiencies of single materials, achieving high sensitivity, rapid response, and excellent stability in humidity detection. However, existing composite material humidity sensors suffer from the following problems: the composite materials are mostly metal oxides and polymers, which can lead to the agglomeration and poor dispersibility of the metal oxides, affecting sensing performance; and existing humidity sensors are mostly fabricated using methods such as spin coating, dip coating, and spray coating, resulting in limited specific surface area and restricting the improvement of sensitivity. Summary of the Invention
[0006] The purpose of this invention is to provide a chitosan-zinc oxide composite nanofiber humidity sensor and its preparation method, so as to solve the problem of poor sensitivity performance of existing humidity sensors.
[0007] The objective of this invention can be achieved through the following technical solutions: This invention provides a chitosan-zinc oxide composite nanofiber humidity sensor, characterized in that it comprises the following components: a substrate, interdigitated electrodes, and a humidity-sensitive material layer; the humidity-sensitive material layer covers the surface of the interdigitated electrodes on the substrate; the humidity-sensitive material layer is a chitosan-zinc oxide composite nanofiber membrane with a thickness of 5-50 μm and a nanofiber diameter of 100-500 nm. The chitosan-zinc oxide composite nanofiber membrane is formed by electrospinning a spinning solution of phosphorylated modified nano zinc oxide, glutaraldehyde and chitosan solution directly deposited on the surface of interdigitated electrodes on a substrate. The phosphorylated modified nano zinc oxide is obtained by reacting nano zinc oxide with an aminosilane coupling agent to obtain modified nano zinc oxide, and then reacting it with phosphoric acid.
[0008] Through the synergistic effect of aminosilane coupling agent modification, phosphorylation modification, and glutaraldehyde crosslinking, uniform dispersion and strong interfacial bonding of nano-zinc oxide in chitosan were achieved. The aminosilane coupling agent and phosphoric acid modification introduced phosphate groups into the nano-zinc oxide. These phosphate groups act as both proton donors and acceptors, providing abundant protons and an efficient transport channel. Combined with the synergistic effect of the semiconductor properties of nano-zinc oxide and the ionic conductivity of chitosan, the conductivity of the composite material was significantly improved.
[0009] Furthermore, the substrate is made of one of PET, PI, or ceramic.
[0010] Furthermore, the interdigitated electrodes are made of either gold or silver.
[0011] Furthermore, the aminosilane coupling agent is one of 3-aminopropyldiethoxymethylsilane, 3-aminopropyltrimethoxysilane, and 3-aminopropyltriethoxysilane.
[0012] Furthermore, the particle size of the nano zinc oxide is 20-100 nm.
[0013] This invention provides a method for preparing a chitosan-zinc oxide composite nanofiber humidity sensor, characterized in that the method for preparing the chitosan-zinc oxide composite nanofiber humidity sensor as described above includes the following steps: S1: Add aminosilane coupling agent to nano zinc oxide ethanol aqueous dispersion and react at 60-80℃ for 4-8h to obtain modified nano zinc oxide; S2: Disperse the modified nano zinc oxide obtained in S1 into a mixture of formaldehyde and phosphoric acid, and react at 50-90℃ for 4-12 h to obtain phosphorylated modified nano zinc oxide. S3: Dissolve chitosan in an aqueous acetic acid solution to obtain a chitosan solution. Disperse the phosphorylated modified nano zinc oxide obtained in S2 into the chitosan solution to obtain a mixture. Add glutaraldehyde to the mixture and mix evenly to obtain a spinning solution. S4: Electrospin the spinning solution obtained in S3, and the fibers are directly deposited on the surface of the interdigitated electrode on the substrate to obtain a nanofiber membrane. The membrane is reacted at 40-60℃ for 2-4 hours, then heated to 80-120℃ and heat-treated for 0.5-1 hours to obtain the humidity sensor.
[0014] Electrospinning endows the nanofiber membrane with a high specific surface area and porous structure, increasing the adsorption sites for water molecules. The use of glutaraldehyde for cross-linking enhances the degree of cross-linking between chitosan molecules, improving the sensor's water resistance and mechanical strength, and ensuring its long-term stability. The three-dimensional network structure formed by hydrogen bonds and chemical cross-linking provides abundant channels for proton transport.
[0015] Furthermore, the aminosilane coupling agent accounts for 0.5-3% of the mass of nano zinc oxide.
[0016] Furthermore, the phosphoric acid has a mass fraction of 85%, and the phosphoric acid accounts for 30-240% of the mass of the modified nano zinc oxide.
[0017] Furthermore, the mass concentration of the chitosan solution is 2-8 wt%.
[0018] Furthermore, the phosphorylated modified nano zinc oxide accounts for 30%-50% of the chitosan mass.
[0019] Furthermore, the glutaraldehyde accounts for 0.5-1.5% of the mass of chitosan.
[0020] Furthermore, the electrospinning includes the following parameters: voltage of 10-25kV, feed speed of 0.5-2mL / h, receiving distance of 10-20cm, temperature of room temperature, and relative humidity of 30-50%RH.
[0021] The beneficial effects of this invention are: 1. This invention achieves uniform dispersion and strong interfacial bonding of nano-zinc oxide in chitosan through the synergistic effect of aminosilane coupling agent modification, phosphoric acid modification, and glutaraldehyde crosslinking. Surface modification of nano-zinc oxide with aminosilane coupling agent and phosphorylation effectively solves the problem of nanoparticle aggregation in the chitosan matrix; phosphoric acid-modified nano-zinc oxide forms hydrogen bonds with chitosan, and the aldehyde groups on the glutaraldehyde molecule undergo an amino-aldehyde condensation reaction with the amino groups on the chitosan molecular chain to form imine bonds, resulting in an interfacial bonding strength far superior to that of physical mixing.
[0022] 2. This invention introduces phosphate groups onto the surface of nano-zinc oxide through an aminosilane coupling agent and phosphoric acid modification. The aminosilane coupling agent combines with nano-zinc oxide to form Si-O-Zn bonds, introducing amino groups onto the surface of nano-zinc oxide. Under the action of formaldehyde, the phosphate groups and amino groups are linked by NCP bonds. The phosphate groups act as both proton donors and acceptors, providing abundant protons and an efficient transport channel for protons. Combined with the semiconductor properties of nano-zinc oxide and the ionic conductivity of chitosan, the conductivity of the composite material is significantly improved.
[0023] 3. The nanofiber membrane obtained by electrospinning in this invention has a high specific surface area and porous structure, increasing the adsorption sites for water molecules. The use of glutaraldehyde for cross-linking improves the degree of cross-linking between chitosan molecules, enhancing the sensor's water resistance and mechanical strength, and ensuring its long-term stability. The three-dimensional network structure formed by hydrogen bonds and chemical cross-linking provides abundant channels for proton transport, potentially enabling highly sensitive and rapidly recovering humidity detection.
[0024] 4. The humidity sensor provided by this invention has a natural dual advantage: chitosan, as a widely available natural polymer, possesses excellent biodegradability and biocompatibility; and nano-zinc oxide has low cytotoxicity. Furthermore, electrospinning can rapidly form a continuous nanofiber network at room temperature and pressure, resulting in a simple process with low energy consumption and low cost. Detailed Implementation
[0025] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0026] Preparation Example 1 The synthesis method of modified nano zinc oxide is as follows: 2 g of nano-zinc oxide was added to 100 mL of an ethanol-water solution (deionized water to anhydrous ethanol volume ratio of 1:9) and ultrasonically dispersed for 90 min to obtain a nano-zinc oxide dispersion. 0.02 g of 3-aminopropyldiethoxymethylsilane was dissolved in 20 mL of anhydrous ethanol. The above 3-aminopropyldiethoxymethylsilane ethanol solution was added dropwise to the above nano-zinc oxide dispersion, and the reaction was carried out at 80 °C for 6 h. The mixture was then centrifuged at 8000 rpm for 10 min, and the supernatant was discarded. The precipitate was washed successively with anhydrous ethanol and deionized water. After washing, the mixture was centrifuged to remove impurities. The precipitate was dried at 60 °C for 8 h to obtain modified nano-zinc oxide.
[0027] Preparation Example 2 The synthesis method of modified nano zinc oxide is as follows: 2 g of nano-zinc oxide was added to 100 mL of an ethanol-water solution (deionized water to anhydrous ethanol volume ratio of 1:9) and ultrasonically dispersed for 90 min to obtain a nano-zinc oxide dispersion. 0.01 g of 3-aminopropyldiethoxymethylsilane was dissolved in 20 mL of anhydrous ethanol. The above 3-aminopropyldiethoxymethylsilane ethanol solution was added dropwise to the above nano-zinc oxide dispersion, and the reaction was carried out at 80 °C for 6 h. The mixture was then centrifuged at 8000 rpm for 10 min, and the supernatant was discarded. The precipitate was washed successively with anhydrous ethanol and deionized water, and centrifuged after washing to remove impurities. The precipitate was dried at 60 °C for 8 h to obtain modified nano-zinc oxide.
[0028] Preparation Example 3 The synthesis method of modified nano zinc oxide is as follows: 2 g of nano-zinc oxide was added to 100 mL of an ethanol-water solution (deionized water to anhydrous ethanol volume ratio of 1:9) and ultrasonically dispersed for 90 min to obtain a nano-zinc oxide dispersion. 0.06 g of 3-aminopropyldiethoxymethylsilane was dissolved in 20 mL of anhydrous ethanol. The above 3-aminopropyldiethoxymethylsilane ethanol solution was added dropwise to the above nano-zinc oxide dispersion, and the reaction was carried out at 80 °C for 6 h. The mixture was then centrifuged at 8000 rpm for 10 min, and the supernatant was discarded. The precipitate was washed successively with anhydrous ethanol and deionized water, and centrifuged after washing to remove impurities. The precipitate was dried at 60 °C for 8 h to obtain modified nano-zinc oxide.
[0029] Preparation Example 4 The synthesis method of phosphorylated modified nano zinc oxide includes the following steps: 1 g of the modified nano zinc oxide prepared in Preparation Example 1 was added to 50 mL of deionized water and ultrasonically dispersed for 30 min. Then, 0.8 g of formaldehyde aqueous solution (mass fraction 37%) and 1.2 g of phosphoric acid (mass fraction 85%) were added sequentially. The mixture was reacted at 70 °C for 12 h under a nitrogen atmosphere. The precipitate was collected by centrifugation at 8000 rpm for 10 min, washed with deionized water until the washing solution was neutral, and dried at 60 °C for 12 h to obtain phosphorylated modified nano zinc oxide.
[0030] Preparation Example 5 The synthesis method of phosphorylated modified nano zinc oxide includes the following steps: 1 g of the modified nano zinc oxide prepared in Preparation Example 1 was added to 50 mL of deionized water and ultrasonically dispersed for 30 min. Then, 0.2 g of formaldehyde aqueous solution (mass fraction of 37%) and 0.3 g of phosphoric acid (mass fraction of 85%) were added sequentially. The mixture was reacted at 70 °C for 12 h under a nitrogen atmosphere. The precipitate was collected by centrifugation at 8000 rpm for 10 min, washed with deionized water until the washing solution was neutral, and dried at 60 °C for 12 h to obtain phosphorylated modified nano zinc oxide.
[0031] Preparation Example 6 The synthesis method of phosphorylated modified nano zinc oxide includes the following steps: 1 g of the modified nano zinc oxide prepared in Preparation Example 1 was added to 50 mL of deionized water and ultrasonically dispersed for 30 min. Then, 1.6 g of formaldehyde aqueous solution (mass fraction 37%) and 2.4 g of phosphoric acid (mass fraction 85%) were added sequentially. The mixture was reacted at 70 °C for 12 h under a nitrogen atmosphere. The precipitate was collected by centrifugation at 8000 rpm for 10 min, washed with deionized water until the washing solution was neutral, and dried at 60 °C for 12 h to obtain phosphorylated modified nano zinc oxide.
[0032] Preparation Example 7 The synthesis method of phosphorylated modified nano zinc oxide includes the following steps: 1 g of the modified nano zinc oxide prepared in Preparation Example 2 was added to 50 mL of deionized water and ultrasonically dispersed for 30 min. Then, 0.8 g of formaldehyde aqueous solution (mass fraction 37%) and 1.2 g of phosphoric acid (mass fraction 85%) were added sequentially. The mixture was reacted at 70 °C for 12 h under a nitrogen atmosphere. The precipitate was collected by centrifugation at 8000 rpm for 10 min, washed with deionized water until the washing solution was neutral, and dried at 60 °C for 12 h to obtain phosphorylated modified nano zinc oxide.
[0033] Preparation Example 8 The synthesis method of phosphorylated modified nano zinc oxide includes the following steps: 1 g of the modified nano zinc oxide prepared in Preparation Example 3 was added to 50 mL of deionized water and ultrasonically dispersed for 30 min. Then, 0.8 g of formaldehyde aqueous solution (mass fraction 37%) and 1.2 g of phosphoric acid (mass fraction 85%) were added sequentially. The mixture was reacted at 70 °C for 12 h under a nitrogen atmosphere. The precipitate was collected by centrifugation at 8000 rpm for 10 min, washed with deionized water until the washing solution was neutral, and dried at 60 °C for 12 h to obtain phosphorylated modified nano zinc oxide.
[0034] Example 1 Step 1: Add 5g of chitosan to 100mL of 2wt% acetic acid aqueous solution and stir until completely dissolved. Add 2g of phosphorylated modified nano-zinc oxide prepared in Preparation Example 4 to the above chitosan solution and ultrasonically disperse for 30min to ensure uniform dispersion of phosphorylated modified nano-zinc oxide. Add 0.1mL of glutaraldehyde aqueous solution (50% by mass) to the above mixture and stir at room temperature for 30min to obtain the electrospinning solution.
[0035] Step 2: Inject the electrospinning solution obtained in Step 1 into a syringe and place it on an electrospinning apparatus. Electrospinning is performed at room temperature and 40% RH, under conditions of 20 kV voltage, a receiving distance of 15 cm, and a feed rate of 1.0 mL / h. The fibers are directly deposited on the surface of interdigitated electrodes (made of gold) on a substrate (ceramic material). A nanofiber membrane with a thickness of 30 μm and a fiber diameter of 200 nm is obtained.
[0036] Step 3: Place the nanofiber membrane obtained in Step 2, along with the substrate and interdigitated electrodes, in a vacuum oven and react at 60°C for 4 hours to allow glutaraldehyde and chitosan to fully cross-link. Dry at 100°C for 0.5 hours to obtain the humidity sensor.
[0037] Example 2 The only difference from Example 1 is that the phosphorylated modified nano-zinc oxide prepared in Example 4 is replaced by the same mass of the phosphorylated modified nano-zinc oxide prepared in Example 7. All other steps and conditions are the same as in Example 1.
[0038] Example 3 The only difference from Example 1 is that the phosphorylated modified nano-zinc oxide prepared in Example 4 was replaced by the same mass of the phosphorylated modified nano-zinc oxide prepared in Example 8. All other steps and conditions were the same as in Example 1.
[0039] Example 4 The only difference from Example 1 is that the phosphorylated modified nano-zinc oxide prepared in Example 4 is replaced by the same mass of the phosphorylated modified nano-zinc oxide prepared in Example 5. All other steps and conditions are the same as in Example 1.
[0040] Example 5 The only difference from Example 1 is that the phosphorylated modified nano-zinc oxide prepared in Example 4 is replaced by the same mass of the phosphorylated modified nano-zinc oxide prepared in Example 6. All other steps and conditions are the same as in Example 1.
[0041] Example 6 The only difference from Example 1 is that the mass of the phosphorylated modified nano zinc oxide prepared in Example 4 was adjusted to 0.8 g; the mass of chitosan was adjusted to 2 g; and the volume of the glutaraldehyde aqueous solution (mass fraction of 50%) was adjusted to 0.04 mL. Other steps and conditions were the same as in Example 1.
[0042] Step 1: Add 2g of chitosan to 100mL of 2wt% acetic acid aqueous solution and stir until completely dissolved. Add 0.8g of phosphorylated modified nano-zinc oxide prepared in Preparation Example 4 to the above chitosan solution and ultrasonically disperse for 30min to ensure uniform dispersion of phosphorylated modified nano-zinc oxide. Add 0.04mL of glutaraldehyde aqueous solution (50% by mass) to the above mixture and stir at room temperature for 30min to obtain electrospinning solution.
[0043] Step 2: Inject the electrospinning solution obtained in Step 1 into a syringe and place it on an electrospinning apparatus. Electrospinning is performed at room temperature and 40% RH, under conditions of 20 kV voltage, a receiving distance of 15 cm, and a feed rate of 1.0 mL / h. The fibers are directly deposited on the surface of interdigitated electrodes (made of gold) on a substrate (ceramic material). A nanofiber membrane with a thickness of 30 μm and a fiber diameter of 200 nm is obtained.
[0044] Step 3: Place the nanofiber membrane obtained in Step 2, along with the substrate and interdigitated electrodes, in a vacuum oven and react at 60°C for 4 hours to allow glutaraldehyde and chitosan to fully cross-link. Dry at 100°C for 0.5 hours to obtain the humidity sensor.
[0045] Example 7 The only difference from Example 1 is that the mass of the phosphorylated modified nano zinc oxide prepared in Example 4 was adjusted to 3.2 g; the mass of chitosan was adjusted to 8 g; and the volume of the glutaraldehyde aqueous solution (mass fraction of 50%) was adjusted to 0.16 mL. Other steps and conditions were the same as in Example 1.
[0046] Step 1: Add 8g of chitosan to 100mL of 2wt% acetic acid aqueous solution and stir until completely dissolved. Add 3.2g of phosphorylated modified nano-zinc oxide prepared in Preparation Example 4 to the above chitosan solution and ultrasonically disperse for 30min to ensure uniform dispersion of phosphorylated modified nano-zinc oxide. Add 0.16mL of glutaraldehyde aqueous solution (50% by mass) to the above mixture and stir at room temperature for 30min to obtain electrospinning solution.
[0047] Step 2: Inject the electrospinning solution obtained in Step 1 into a syringe and place it on an electrospinning apparatus. Electrospinning is performed at room temperature and 40% RH, under conditions of 20 kV voltage, a receiving distance of 15 cm, and a feed rate of 1.0 mL / h. The fibers are directly deposited on the surface of interdigitated electrodes (made of gold) on a substrate (ceramic material). A nanofiber membrane with a thickness of 30 μm and a fiber diameter of 200 nm is obtained.
[0048] Step 3: Place the nanofiber membrane obtained in Step 2, along with the substrate and interdigitated electrodes, in a vacuum oven and react at 60°C for 4 hours to allow glutaraldehyde and chitosan to fully cross-link. Dry at 100°C for 0.5 hours to obtain the humidity sensor.
[0049] Example 8 The only difference from Example 1 is that the mass of the phosphorylated modified nano zinc oxide prepared in Preparation Example 4 was adjusted to 1.5 g. The other steps and conditions were the same as in Example 1.
[0050] Step 1: Add 5g of chitosan to 100mL of 2wt% acetic acid aqueous solution and stir until completely dissolved. Add 1.5g of phosphorylated modified nano-zinc oxide prepared in Preparation Example 4 to the above chitosan solution and ultrasonically disperse for 30min to ensure uniform dispersion of phosphorylated modified nano-zinc oxide. Add 0.1mL of glutaraldehyde aqueous solution (50% by mass) to the above mixture and stir at room temperature for 30min to obtain electrospinning solution.
[0051] Step 2: Inject the electrospinning solution obtained in Step 1 into a syringe and place it on an electrospinning apparatus. Electrospinning is performed at room temperature and 40% RH, under conditions of 20 kV voltage, a receiving distance of 15 cm, and a feed rate of 1.0 mL / h. The fibers are directly deposited on the surface of interdigitated electrodes (made of gold) on a substrate (ceramic material). A nanofiber membrane with a thickness of 30 μm and a fiber diameter of 200 nm is obtained.
[0052] Step 3: Place the nanofiber membrane obtained in Step 2, along with the substrate and interdigitated electrodes, in a vacuum oven and react at 60°C for 4 hours to allow glutaraldehyde and chitosan to fully cross-link. Dry at 100°C for 0.5 hours to obtain the humidity sensor.
[0053] Example 9 The only difference from Example 1 is that the mass of the phosphorylated modified nano zinc oxide prepared in Preparation Example 4 was adjusted to 2.5 g. All other steps and conditions were the same as in Example 1.
[0054] Step 1: Add 5g of chitosan to 100mL of 2wt% acetic acid aqueous solution and stir until completely dissolved. Add 2.5g of phosphorylated modified nano-zinc oxide prepared in Preparation Example 4 to the above chitosan solution and ultrasonically disperse for 30min to ensure uniform dispersion of phosphorylated modified nano-zinc oxide. Add 0.1mL of glutaraldehyde aqueous solution (50% by mass) to the above mixture and stir at room temperature for 30min to obtain the electrospinning solution.
[0055] Step 2: Inject the electrospinning solution obtained in Step 1 into a syringe and place it on an electrospinning apparatus. Electrospinning is performed at room temperature and 40% RH, under conditions of 20 kV voltage, a receiving distance of 15 cm, and a feed rate of 1.0 mL / h. The fibers are directly deposited on the surface of interdigitated electrodes (made of gold) on a substrate (ceramic material). A nanofiber membrane with a thickness of 30 μm and a fiber diameter of 200 nm is obtained.
[0056] Step 3: Place the nanofiber membrane obtained in Step 2, along with the substrate and interdigitated electrodes, in a vacuum oven and react at 60°C for 4 hours to allow glutaraldehyde and chitosan to fully cross-link. Dry at 100°C for 0.5 hours to obtain the humidity sensor.
[0057] Example 10 The only difference from Example 1 is that the volume of the glutaraldehyde aqueous solution (50% by mass) is adjusted to 0.05 mL. The other steps and conditions are the same as in Example 1.
[0058] Step 1: Add 5g of chitosan to 100mL of 2wt% acetic acid aqueous solution and stir until completely dissolved. Add 2g of phosphorylated modified nano-zinc oxide prepared in Preparation Example 4 to the above chitosan solution and ultrasonically disperse for 30min to ensure uniform dispersion of phosphorylated modified nano-zinc oxide. Add 0.05mL of glutaraldehyde aqueous solution (50% by mass) to the above mixture and stir at room temperature for 30min to obtain the electrospinning solution.
[0059] Step 2: Inject the electrospinning solution obtained in Step 1 into a syringe and place it on an electrospinning apparatus. Electrospinning is performed at room temperature and 40% RH, under conditions of 20 kV voltage, a receiving distance of 15 cm, and a feed rate of 1.0 mL / h. The fibers are directly deposited on the surface of interdigitated electrodes (made of gold) on a substrate (ceramic material). A nanofiber membrane with a thickness of 30 μm and a fiber diameter of 200 nm is obtained.
[0060] Step 3: Place the nanofiber membrane obtained in Step 2, along with the substrate and interdigitated electrodes, in a vacuum oven and react at 60°C for 4 hours to allow glutaraldehyde and chitosan to fully cross-link. Dry at 100°C for 0.5 hours to obtain the humidity sensor.
[0061] Example 11 The only difference from Example 1 is that the volume of the glutaraldehyde aqueous solution (50% by mass) is adjusted to 0.15 mL. The other steps and conditions are the same as in Example 1.
[0062] Step 1: Add 5g of chitosan to 100mL of 2wt% acetic acid aqueous solution and stir until completely dissolved. Add 2g of phosphorylated modified nano-zinc oxide prepared in Preparation Example 4 to the above chitosan solution and ultrasonically disperse for 30min to ensure uniform dispersion of phosphorylated modified nano-zinc oxide. Add 0.15mL of glutaraldehyde aqueous solution (50% by mass) to the above mixture and stir at room temperature for 30min to obtain the electrospinning solution.
[0063] Step 2: Inject the electrospinning solution obtained in Step 1 into a syringe and place it on an electrospinning apparatus. Electrospinning is performed at room temperature and 40% RH, under conditions of 20 kV voltage, a receiving distance of 15 cm, and a feed rate of 1.0 mL / h. The fibers are directly deposited on the surface of interdigitated electrodes (made of gold) on a substrate (ceramic material). A nanofiber membrane with a thickness of 30 μm and a fiber diameter of 200 nm is obtained.
[0064] Step 3: Place the nanofiber membrane obtained in Step 2, along with the substrate and interdigitated electrodes, in a vacuum oven and react at 60°C for 4 hours to allow glutaraldehyde and chitosan to fully cross-link. Dry at 100°C for 0.5 hours to obtain the humidity sensor.
[0065] Comparative Example 1 The only difference from Example 1 is that the phosphorylated modified zinc oxide prepared in Example 4 was directly replaced by an equal mass of nano zinc oxide. All other steps and conditions were the same as in Example 1.
[0066] Comparative Example 2 The only difference from Example 7 is that the electrospinning was performed directly with chitosan without the addition of phosphorylated modified nano zinc oxide and glutaraldehyde.
[0067] Step 1: Add 5g of chitosan to 100mL of acetic acid aqueous solution with a mass concentration of 2wt%, and stir until completely dissolved to obtain electrospinning solution.
[0068] Step 2: Inject the electrospinning solution obtained in Step 1 into a syringe and place it on an electrospinning apparatus. Electrospinning is performed at room temperature and 240% RH, under conditions of 20 kV voltage, a receiving distance of 15 cm, and a feed rate of 1.0 mL / h. The fibers are directly deposited on the surface of interdigitated electrodes (made of gold) on a substrate (ceramic material). A nanofiber membrane with a thickness of 30 μm and a fiber diameter of 100-500 nm is obtained.
[0069] Step 3: Place the nanofiber membrane obtained in Step 2, along with the substrate and interdigitated electrodes, in a vacuum oven and dry at 100°C for 0.5 hours to obtain a humidity sensor.
[0070] Test method: The humidity sensor of this invention was tested using the fixed humidity of saturated salt solutions. Nine salts (LiCl, KAc, MgCl2, K2CO3, Mg(NO3)2, CuCl2, NaCl, KCl, and K2SO4) with different humidity levels at saturation were selected. Saturated solutions were prepared and placed in a desiccator. After the solution humidity stabilized, the test was conducted at room temperature. The humidity levels were as follows: LiCl 11% RH, KAc 23% RH, MgCl2 33% RH, K2CO3 43% RH, Mg(NO3)2 55% RH, CuCl2 67% RH, NaCl 75% RH, KCl 86% RH, and K2SO4 98% RH.
[0071] Linear response test: Different saturated salt water was placed at the bottom of each of the nine desiccators, and humidity sensors were placed on the desiccator partitions. After the above devices were placed in a constant temperature and humidity chamber for equilibration for 30 minutes, the resistance was measured at each humidity level, response curves were plotted, and linear fitting was performed.
[0072] Response and recovery time test: The system rapidly switches between two humidity environments, 11% RH and 98% RH. The time required for the signal change to reach 90% of the final stable value is recorded as the response time and recovery time, respectively. The test is repeated 5 times and the average value is taken.
[0073] Long-term stability test: The test was conducted in accordance with the JEDEC JESD22-A101 standard. Three parallel samples were placed in a constant temperature and humidity test chamber at 85℃ / 85% RH and run continuously for 1000 hours. The samples were then removed, dried in a desiccator at room temperature for 24 hours, and then retested. The performance degradation rate was calculated as the percentage deviation of the parameters after aging from the initial parameters.
[0074]
[0075] Performance tests were conducted on Examples 1-11 and Comparative Examples 1-2, and the results are shown in Table 1: Table 1
[0076] As shown in Table 1, compared to Comparative Examples 1-2, Examples 1-11 all exhibit faster response and recovery times, a better linear relationship between humidity and resistance, and lower performance degradation rates (better long-term stability). This is because the examples achieve highly sensitive and rapidly recovering humidity detection through the synergistic effect of aminosilane coupling agent modification, phosphoric acid modification, and glutaraldehyde crosslinking. Surface modification of nano-zinc oxide with aminosilane coupling agent and phosphoric acid effectively solves the problem of nanoparticle aggregation in the chitosan matrix. The phosphate groups act as both proton acceptors and proton donors, providing abundant protons and an efficient transport channel. The semiconductor properties of nano-zinc oxide synergistically enhance the conductivity of the composite material. Glutaraldehyde further strengthens the crosslinking between chitosan particles, preventing swelling of chitosan in high humidity environments and improving the long-term stability of the material.
[0077] Of Examples 1-3, Example 1 exhibited the best performance because Example 2 had a lower proportion of aminosilane coupling agent, while Example 3 had a higher proportion. A lower proportion resulted in insufficient phosphate for subsequent modification, affecting proton transport; while a higher proportion led to nanoparticle aggregation, decreased dispersibility, and reduced performance.
[0078] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus.
[0079] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A chitosan-zinc oxide composite nanofiber humidity sensor, characterized in that, It comprises the following components: a substrate, interdigitated electrodes, and a humidity-sensitive material layer; the humidity-sensitive material layer covers the surface of the interdigitated electrodes on the substrate; the humidity-sensitive material layer is a chitosan-zinc oxide composite nanofiber membrane with a thickness of 5-50 μm and a nanofiber diameter of 100-500 nm. The chitosan-zinc oxide composite nanofiber membrane is formed by electrospinning a spinning solution of phosphorylated modified nano zinc oxide, glutaraldehyde and chitosan solution directly deposited on the surface of interdigitated electrodes on a substrate. The phosphorylated modified nano zinc oxide is obtained by reacting nano zinc oxide with an aminosilane coupling agent to obtain modified nano zinc oxide, and then reacting it with phosphoric acid.
2. The chitosan-zinc oxide composite nanofiber humidity sensor according to claim 1, characterized in that, The substrate is made of one of the following materials: PET, PI, or ceramic.
3. The chitosan-zinc oxide composite nanofiber humidity sensor according to claim 1, characterized in that, The interdigitated electrodes are made of either gold or silver.
4. The chitosan-zinc oxide composite nanofiber humidity sensor according to claim 1, characterized in that, The aminosilane coupling agent is one of 3-aminopropyldiethoxymethylsilane, 3-aminopropyltrimethoxysilane, and 3-aminopropyltriethoxysilane.
5. The chitosan-zinc oxide composite nanofiber humidity sensor according to claim 1, characterized in that, The particle size of the nano zinc oxide is 20-100 nm.
6. A method for preparing a chitosan-zinc oxide composite nanofiber humidity sensor, characterized in that, The preparation of the chitosan-zinc oxide composite nanofiber humidity sensor as described in any one of claims 1-5 includes the following steps: S1: Add aminosilane coupling agent to nano zinc oxide ethanol aqueous dispersion and react at 60-80℃ for 4-8h to obtain modified nano zinc oxide; S2: Disperse the modified nano zinc oxide obtained in S1 into a mixture of formaldehyde and phosphoric acid, and react at 50-90℃ for 4-12 h to obtain phosphorylated modified nano zinc oxide. S3: Dissolve chitosan in an aqueous acetic acid solution to obtain a chitosan solution. Disperse the phosphorylated modified nano zinc oxide obtained in S2 into the chitosan solution to obtain a mixture. Add glutaraldehyde to the mixture and mix evenly to obtain a spinning solution. S4: Electrospin the spinning solution obtained in S3, and the fibers are directly deposited on the surface of the interdigitated electrode on the substrate to obtain a nanofiber membrane. The membrane is reacted at 40-60℃ for 2-4 hours, then heated to 80-120℃ and heat-treated for 0.5-1 hours to obtain the humidity sensor.
7. The method for preparing a chitosan-zinc oxide composite nanofiber humidity sensor according to claim 6, characterized in that, The aminosilane coupling agent accounts for 0.5-3% of the mass of nano zinc oxide.
8. The method for preparing a chitosan-zinc oxide composite nanofiber humidity sensor according to claim 6, characterized in that, The phosphoric acid has a mass fraction of 85%, and accounts for 30-240% of the mass of the modified nano zinc oxide.
9. The method for preparing a chitosan-zinc oxide composite nanofiber humidity sensor according to claim 6, characterized in that, The chitosan solution has a mass concentration of 2-8 wt%; the phosphorylated modified nano zinc oxide accounts for 30-50% of the chitosan mass; and the glutaraldehyde accounts for 0.5-1.5% of the chitosan mass.
10. The method for preparing a chitosan-zinc oxide composite nanofiber humidity sensor according to claim 6, characterized in that, The electrospinning process includes the following parameters: voltage of 10-25kV, feed speed of 0.5-2mL / h, receiving distance of 10-20cm, temperature of room temperature, and relative humidity of 30-50%RH.